Educational Support for Career Development of South Sulawesi Athletes - Arifuddin Usman; Suroto; Nining Widyah Kusnanik; Arimbi; Poppy Elisano Arfanda (Universitas Negeri Semarang, 2024)
This research aims to evaluate the form of educational services for students who are also pursuing professions as outstanding athletes. In general, outstanding athletes often face a dilemma when faced with the obligations they also have to carry out in their formal education. Starting from class schedules, and assignments to exams that they have to complete during training and match schedules. This research involved 34 outstanding student-athletes who had at least won a bronze medal in a South Sulawesi provincial-level championship event. This research will analyze the context, input, processes, and products of existing educational services, including distance programs, special athlete schools, and programs at sports training centers. The goal is to identify problems and suitability of available special education services and create a destination where athletes can excel in both sports and academics. The conclusion obtained in this research is that at the primary to secondary education level, there are no special regulations made by schools to accommodate outstanding student-athletes as a form of support for student-athlete careers. Another interesting finding in this research was that 90% of student-athlete respondents preferred and understood practical lecture material more easily than theoretical material.